Methylation associated with long- or short-term survival in glioblastoma patients from the Nordic phase 3 trial - Łysiak, Małgorzata; Das, Jyotirmoy; Malmström, Annika; Söderkvist, Peter (Frontiers in Genetics, 2022)
Patients with glioblastoma (GBM) have a poor outcome, but even among patients receiving the same therapies and with good prognostic factors, one can find those with exceptionally short and long survival. From the Nordic trial, which randomized GBM patients 60 years or older between 2 radiotherapy arms (60Gy or 34Gy) or temozolomide (TMZ), we selected 59 with good prognostic factors. These were equally distributed according to treatment and MGMT promoter methylation status but had long or short survival. Methylation profiling with the Illumina Infinium Methylation EPIC BeadChip arrays was performed and utilized for methylation-based CNS tumor classification, pathway enrichment analysis of differentially methylated CpG sites (DMCs), as well as calculation of epigenetic age acceleration with three different algorithms to compare the long and short survival groups. Samples identified by the classifier as non-GBM IDH wildtype were excluded. DMCs between long- and short-term survivors were found in patients with methylated MGMT promoter treated with TMZ (123,510), those with unmethylated MGMT treated with 60Gy radiotherapy (4,086) and with methylated MGMT promoter treated with 34Gy (39,649). Long-term survivors with methylated MGMT promoter treated with TMZ exhibited hypermethylation of the Wnt signaling and the platelet activation, signaling and aggregation pathways. The joint analysis of radiotherapy arms revealed 319 DMCs between long- and short-term survivors with unmethylated MGMT and none for samples with methylated MGMT promoter. An analysis comparing epigenetic age acceleration between patients with long- and short-term survival across all treatment arms showed a decreased epigenetic age acceleration for the latter. We identified DMCs for both TMZ and RT treated patients and epigenetic age acceleration as a potential prognostic marker, butfurther systematic analysis of larger patient cohorts is necessary for confirmation of their prognostic and/or predictive properties.